(3GdESJKeGQ aj GdefGWb GdMQIs - (3eMeO bGSe(B, (3NUGhfIs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2010)
(3JYQja HYV GdeUWdMGJ , fTCI GdefGWb GdMQI , GdYhdeI h GdJfGaSjI h OhQ GdefGWb GdMQI , GdOQGSGJ GdSGHbI PGJ GdUdI HGdefGWb GdMQI , ebheGJ EfTGA h YhGed fLGM GdefGWb GdMQI , GdefGWb GddMQI aj GdLeghQjI GdYQHjI GdeUQjI , fThA GdefGWb GdMQI GdGQOfjI h JWhQgG(B.s
(3eQGLY U(B.127s
Keywords: (3GdGSJKeGQs; (3GdJLGQI(B- (3GdefGWb GdMQIs